1991
DOI: 10.1016/0378-1097(91)90447-i
|View full text |Cite
|
Sign up to set email alerts
|

Rapid genotyping of the Chlamydia trachomatis major outer membrane protein by the polymerase chain reaction

Abstract: Twenty one Chlamydia trachomatis reference strains and 40 clinical isolates belonging to the lymphogranuloma venerum (LGV) and trachoma biovars were genotyped by differential restriction mapping of the major-outer-membrane-protein gene (MOMP) obtained by the polymerase-chain reaction (PCR). AluI digestion of the PCR product distinguishes eight MOMP-genotypes corresponding to 8 serovars. Six additional enzymes (NlaIII, CfoI, EcoRI, HinfI, DdeI and FokI) further permit the discrimination of 10 MOMP-genotypes cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
51
2
1

Year Published

1992
1992
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 22 publications
1
51
2
1
Order By: Relevance
“…In addition, because the RLB method uses a nonprecipitating ECL substrate, it has the advantage that nylon filters can be stripped and reused at least 10 times (16). Based on the fact that the VD2 primers are located within the omp1 gene, our RLB system has a further advantage in that it can also be used for typing of the PCR-amplified omp1 gene used for RFLP (4,8,12,13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, because the RLB method uses a nonprecipitating ECL substrate, it has the advantage that nylon filters can be stripped and reused at least 10 times (16). Based on the fact that the VD2 primers are located within the omp1 gene, our RLB system has a further advantage in that it can also be used for typing of the PCR-amplified omp1 gene used for RFLP (4,8,12,13).…”
Section: Discussionmentioning
confidence: 99%
“…These techniques include standard MOMP serotyping, restriction fragment length polymorphism (RFLP) analysis of the PCRamplified omp1 gene, and nucleotide sequencing of the omp1 gene (3,4,12,13,19). Compared to immunotyping, the genotyping methods are more sensitive and specific for C. trachomatis serovar identification.…”
mentioning
confidence: 99%
“…Epidemiological studies of C. trachomatis infections in sexual contacts have been few to date, which hampers the study of chlamydial transmission, its route of spread in a population, its virulence factors, and the associated risk factors of C. trachomatis infections (12,19). Compared with immunotyping, the genotyping methods, particularly omp1 are more sensitive and precise in revealing C. trachomatis variants within serovars as well as in potential recombinants among serovars (13,15,18). The present study was undertaken to understand the occurrence of C. trachomatis serovars in the genital tracts of infected women, which will help in devising an effective screening program for routine diagnosis of chlamydial infections, understanding the immunopathogenesis, and developing an effective chlamydial control program.…”
mentioning
confidence: 99%
“…Serovars A-C are most often associated with trachoma and serovars L1-L3 are associated with lymphogranuloma venereum, while serovars D-K are primarily associated with urogenital and neonatarum infections (Morré et al, 1998a;Ossewaarde et al, 1994;Sturm-Ramirez et al, 2000). Various studies have shown the feasibility of typing clinical isolates by PCR-based RFLP analysis of the amplified omp1 gene encoding MOMP (Frost et al, 1991;Rodriguez et al, 1991;Sayada et al, 1991), avoiding the costly production of monoclonal antibodies. This method was originally performed on cell cultures of cervical and urethral specimens.…”
Section: Introductionmentioning
confidence: 99%